2010
DOI: 10.4103/0971-9784.62938
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane causes less arrhythmias than desflurane after off-pump coronary artery bypass grafting: A pilot study

Abstract: Ultra-fast track anesthesia using sevoflurane seems more advantageous than desflurane for anesthesia, for OPCABG, as it is associated with significantly less atrial fibrillation or supraventricular arrhythmias after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…It has been shown that some drugs and techniques may lead to the reduction of POAF (Table 3) [119][120][121][122][123][124][125][126][127][128][129][130][131].…”
Section: Other Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that some drugs and techniques may lead to the reduction of POAF (Table 3) [119][120][121][122][123][124][125][126][127][128][129][130][131].…”
Section: Other Interventionsmentioning
confidence: 99%
“…Table 3. Drugs and interventions that might reduce the incidence of postoperative atrial fibrillation High thoracic epidural anesthesia [119] Volatile anesthetics [120] Glucose-insulin-potassium solution [121] Levosimendan [122] Dexmedetomidine [123] N-acetylcysteine [124] Triiodothyronine [125] Vitamin C [126] Miniaturized cardiopulmonary bypass systems [127] Off-pump surgery [128] Leukocyte depletion [129] Minimizing blood transfusions [130] Temperature management during perfusion [131] …”
Section: Electrical Cardioversionmentioning
confidence: 99%
“…No differences in troponin release were reported by other authors when sevoflurane was compared to desflurane and propofol [ 28 ], to propofol in a remifentanil - based anesthesia regime [ 29 , 30 ] and to isoflurane alone [ 31 , 32 ]. Sevoflurane was also showed to have several other benefits: better antioxidative properties than propofol [ 33 ], reduced incidence of arrhythmias compared to desflurane [ 34 ], better preservation of cardiac function compared to control and to propofol [ 35 , 36 ] and to reduced NBP release and plasma protein A release when compared to propofol [ 37 ]. Isoflurane was reported to reduce troponin release when compared to propofol [ 38 ] but no differences were found when compared to sevoflurane [ 31 , 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…Other authors on the contrary did not find differences in terms of troponin release when it was compared to a propofol group of patients [ 39 ]. Desflurane was reported to improve LSWI when compared to a propofol anesthetic regime, although no differences in troponin release were observed [ 40 ], and moreover was found to be less effective in reducing incidence of arrhythmias than sevoflurane [ 34 ]. Guarracino et al observed a significant reduction in troponin release in a cohort of 57 patients anesthetized with desflurane [ 41 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation